PERFORMANCE OF ISLAMIC AND CONVENTIONAL BANKING IN CAMEL ANALYSIS - Ali Farhan (STIE Mahardhika, 2022)
This article tries to compare the financial performance of Islamic banks and conventional banks, to find out which of the two bank models has better performance. The research method used is descriptive with the CAMEL analysis approach, the selected sample is the 2018 monthly financial statements of BRI Syariah, BRI Conventional, Mandiri Syariah, and Mandiri Conventional. The results show that in general the financial performance of conventional banks is better than Islamic banks.